PERAN PARTAI POLITIK TERHADAP LAHIRNYA PERATURAN DAERAH (PERDA) DI PROVINSI RIAU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The existence of a Regional Regulation is an embodiment of thegranting of authority to the Region in managing and regulating its own household,because there are parts of regional affairs besides being regulated in law and mustbe further regulated by regional regulations. In the birth of the PERDA, politicalparties have their own role, because in article 11 paragraph (1) of Law Number 2 of2011 concerning Political Parties, one of the functions of political parties is as ameans to absorb, collect, and channel the political aspirations of society informulating and establish State policies. Likewise in Riau Province, the ProvincialGovernment or the Executive together with the Provincial DPRD has createdPERDA for the Riau Community.This type of research can be classified as sociological juridical, namely aresearch approach that emphasizes the legal aspects regarding the subject matter tobe discussed, associated with the reality in the field. This research was conducted inpolitical parties in Riau Province. Sources of data used are primary data andsecondary data, data collection techniques in this study are by observation,questionnaires, interviews and literature review.In the research results, there are three main points that can be concluded.First, the role of each political party in Riau Province is relatively similar, the onlydifference is the timing of the implementation of policies or programs carried out byparties and also a little difference is that there are a few internal party programsthat are not owned by other parties. Second, that the role of every political party inRiau Province in the formation of regional regulations has been carried out well,even though the parties must be more maximal in carrying out their role. Third Interms of the formation of regional regulations, political parties have based on thetheory of people's sovereignty, because political parties absorb the aspirations of thecommunity, political parties also open space for discussion and direct meetings withthe community.Keywords : Role of Political Parties - Regional Regulations - People's sovereignty